Telepresence in Education. Issue 24 (2015) - Bauer, J.M.; Durakbasa, N.M.; Bas, G.; Guclu, E.; Kopacek, P.
Abstract: New developments of information and media technologies in the evolving landscape of higher education provide efficient and effective training opportunities in higher education. This paper presents a model in new forms of active and collaborative learning that expands the learning environment by using the internet and offering students over telepresence a virtual window on the practical laboratory work in the "High Precision Measuring Room and Nanometrology Laboratory" at the Vienna University of Technology. Establishing requirements of high quality in the education and for related personnel are the fundamentals of this study by establishing a cost-effective project, which enables remote-laboratory operations with an integrated quality management system without any border of working partners. This on-going project is proposed as the example of a global solution to develop a cost-effective approach in education quality not only in Europe but also globally.